SEXUAL VIOLENCE AGAINST CHILDREN: A CASE STUDY ON CHILDREN TREATED DP3AP2KB BENGKULU CITY - Aulia Dira Rizani; Heni Nopianti; Ika Pasca Himawati (SOSIOEDUKASI, 2025)
Violence against children is a complex social problem that has long-term consequences for their physical, psychological, and social development. In Bengkulu City, data from the UPTD PPA DP3AP2KB recorded 97 cases of violence against children during the 2021–2024 period, with molestation and sexual intercourse being the most prevalent forms. This study aims to identify the factors that cause sexual violence against children and to understand the social dynamics underlying these cases. A qualitative descriptive approach was employed, using in-depth interviews, non-participant observation, and documentation. Research informants consisted of child victims, their families, and staff of the UPTD PPA DP3AP2KB Bengkulu City, with a total of five child victims as the main informants. The findings show that sexual violence against children is driven by multiple interrelated factors, including low economic conditions, dysfunctional family roles, low parental education and awareness, the nature of parental employment, as well as exposure to media and peer influences. These factors interact to create conditions that increase children’s vulnerability to violence, particularly within the domestic environment that should function as a place of protection. From a family sociology and structural functionalism perspective, sexual violence against children reflects weakened family functions and insufficient social control in the wider community. The study highlights the need for comprehensive efforts through improved parenting literacy, strengthened child protection systems, and stronger synergy between government institutions, communities, and families to more effectively prevent and address sexual violence against children.  It also bridges theory and practice by linking family level vulnerabilities with institutional responses of DP3AP2KB, offering a reference for future research and child protection policy development.